Trophic and feeding ecology of whale sharks (Rhincodon typus) using bulk stable isotope analysis - Clare E. M. Prebble; Lydie I. E. Couturier; Christoph A. Rohner; Simon J. Pierce; Clive N. Trueman (Frontiers in Fish Science)
IntroductionDespite their size, relatively passive behavior, and commercial significance, knowledge of the behavioral ecology of whale sharks remains limited. The difficulty of tracking individual animals at sea encourages the use of retrospective biochemical approaches such as stable isotope analysis.MethodsWhale sharks at Mafia Island in Tanzania form a comparatively small and resident aggregation that has been monitored for several successive years, providing a rare opportunity to study biochemical changes in individuals over time. In this study, 53% of the identified individuals were sampled at the time of collection over a multi-year period. Stable isotope analysis was performed on these samples to investigate their feeding ecology.ResultsStable isotope data suggest that whale sharks at Mafia Island predominantly feed within the local food web at a trophic level consistent with current understanding of the species' general feeding ecology. These data also reveal a range of individual feeding strategies within the local aggregation, with some sex and size-related differences. However, the isotopic niche area at the population level was relatively constrained.DiscussionWe call for additional research and emphasize the importance of a multi-faceted approach incorporating diverse biochemical and tracking techniques to more accurately understand the long-term feeding ecology of this endangered and charismatic mega-planktivore.